Filtro gravitatorio con piedra pómez molida para el tratamiento primario de aguas residuales porcinas - Mocha Zambrano, Joselyn María (2021)
This research work was carried out on the La Pavita site. It aimed to evaluate the efficiency of the gravitational filter with ground pumice stone as a replacement for fine sand for the primary treatment of swine wastewater. The method used was deductive quantitative with non-experimental level; Techniques such as bibliographical data were also used for filter construction, sampling and data analysis in the programs Microsoft Excel and SPSS. For the first specific objective, the following values were obtained as a result of physicochemical analyses performed on the swine wastewater sample: 580 mg/l for OSH; 581 mg/l for SDT; >190000 UFC/ml for CF; 190000 UFC/ml for total coliforms; and a value of 820 mg/l for COD, parameters that exceed the permissible maximum limits set by TULSMA for discharges to freshwater bodies. Were used for the construction of the filters two plastic buckets with a volume of 20 liters and an area of 0,277 m2. The average retention time of the filters was 1 h 35 min for the sand filter and 1 h 43 min for the pumice stone filter. Removal percentages reached 97, 76% for OSH (pumice filter) as high and lowest for SDT (4,13% and 4,47%, for pity stone and sand filters, respectively). Student's T-test determined that there is no significant difference between the means of the treatments used.